Hospital Ethics Case Consultations: Practical Guidelines - Vaszar, Laszlo T.; Raffin, Thomas A.; Kuschner, Ware G. (Comprehensive therapy, 2005)
Hospital ethics committees provide education, assist in policymaking, and deliver consultation services. In this article, we describe the structure, operation, and institutional framework within which an ethics committee fulfills its missions, with emphasis on the consultation process.